Natural regeneration of Scots pine seedlings in northern Finland after small gap, selection and shelterwood cuttings and site preparation - Peltola, Petra; Maltamo, Matti; Poutiainen, Tuukka; Pääkkönen, Viivi; Petty, Aaron; Yang, Fan; Pikkarainen, Laura; Korhonen, Lauri; Rautio, Pasi; Hallikainen, Ville; Kilpeläinen, Antti; Peltola, Heli (Elsevier, 2026)
The interest in continuous cover forestry (CCF) has increased in Northern Europe over the last decade. Its sustainability depends on successful natural regeneration, which can be limited by the demanding growing conditions in northern Fennoscandia. We studied the early success of, and factors influencing, natural regeneration of Scots pine seedlings on xeric and mesic sites in northern Finland after small gap, selection and shelterwood cuttings and site preparation (none, track and patch scarification). The six study stands treated in 2020–2021 were inventoried in 2024, 3–4 years after cuttings. We evaluated the factors affecting the number of Scots pine seedlings established after cuttings using generalised linear mixed modelling, considering both field-measured and remote-sensing-based predictors. We found that the modelled number of pine seedlings increased in the small gap stands along with increasing distance from the forest edge and coverage of bare humus and lichen. In the selection and shelterwood cutting stands it decreased along with increasing stoniness and moss (excluding Sphagnum spp.) coverage. In both cases, site preparation (especially track preparation) improved the regeneration result. Based on the best fitting model, the mean number of pine seedlings in the small gap stands was 1500 ha−1 and in the selection and shelterwood cutting stands 1000 ha−1. To conclude, the establishment of seedlings was low, but it may increase in the coming years.
Keywords: continuous cover forestry; LiDAR; aerial imaging; track preparation; patch scarification; area-based approach